2013
DOI: 10.4097/kjae.2013.65.3.215
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of feasibility and safety on fiberoptic guided intubation under conscious sedation with remifentanil and propofol

Abstract: BackgroundOropharyngeal manipulation is problematic when patients have a gag reflex. Sedation can suppress gag reflex, but can cause serious airway problems. We compared remifentanil (Group R) and propofol (Group P) in terms of cooperation and loss of gag reflex, while drugs were administered incrementally using target controlled infusion (TCI).MethodsFifty seven patients who required awake fiberoptic intubation were randomized to Group R or Group P. After measurement of baseline gag trigger point index (GTPI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Remifentanil in combination with propofol reduces the total dose of propofol required to achieve deep sedation, resulting in reduced recovery time and reduced severe pain related to sedation. A study comparing the incidences of SGR after the administration of remifentanil and propofol reported that remifentanil is more effective in suppressing GR when the patient can cooperate during the treatment process because propofol has stronger sedative effects than attenuating effects on GR [ 10 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remifentanil in combination with propofol reduces the total dose of propofol required to achieve deep sedation, resulting in reduced recovery time and reduced severe pain related to sedation. A study comparing the incidences of SGR after the administration of remifentanil and propofol reported that remifentanil is more effective in suppressing GR when the patient can cooperate during the treatment process because propofol has stronger sedative effects than attenuating effects on GR [ 10 11 ].…”
Section: Discussionmentioning
confidence: 99%